Comparative analysis of the complete chloroplast genome among Prunus mume, P. armeniaca, and P. salicina. Issue 1 (21st July 2019) - Xue, Song; Shi, Ting; Luo, Wenjie; Ni, Xiaopeng; Iqbal, Shahid; Ni, Zhaojun; Huang, Xiao; Yao, Dan; Shen, Zhijun; Gao, Zhihong
Abstract: Prunus mume Sieb. et Zucc., P . armeniaca L., and P . salicina L. are economically important fruit trees in temperate regions. These species are taxonomically perplexing because of shared interspecific morphological traits and variation, which are mainly attributed to hybridization. The chloroplast is cytoplasmically inherited and often used for evolutionary studies. We sequenced the complete chloroplast genomes of P. mume, P. armeniaca, and P. salicina using Illumina sequencing followed by de novo assembly. The three chloroplast genomes exhibit a typical quadripartite structure with conserved genome arrangement, structure, and moderate divergence. The lengths of the genomes are 157, 815, 157, 797, and 157, 916 bp, respectively. The length of the large single-copy region (LSC) region is 86, 113, 86, 283, and 86, 122 bp, and the length of the SSC region is 18, 916, 18, 734, and 19, 028 bp; the IR region is 26, 393, 26, 390, and 26, 383 bp, respectively. Each of the three chloroplast genomes encodes 133 genes, including 94 protein-coding, 31 tRNA, and eight rRNA genes. Differential gene analysis for the three species revealed that trnY-ATA is a unique gene in P. armeniaca ; in contrast, the gene trnI-TAT is only present in P. mume and P. salicina, though the position of the gene in these chloroplast genomes differs. Further comparative analysis of the complete chloroplast genome sequences revealed that the ORF genes and the sequences of linked regions rps16 and atpA, atpH and atpI, trnc-GCA and psbD, ycf3 and atpB, and rpL32 and ndhD are significantly different and may be used as molecular markers in taxonomic studies. Phylogenetic evolution analysis of the three species suggests that P. mume has a closer genetic relationship to P. armeniaca than to P. salicina .